Move ( 5x) to the left side of the equation by subtracting it from both sides. ( 3x^2-5x=0) Use the quadratic formula to find the solutions. ( (-b± √(b^2-4(ac)))/(2a)) Substitute the values ( a=3), ( b=-5), and ( c=0) into the quadratic formula and solve for ...
Solve using the quadratic equation. 5r^2 = 2r + 1 Solve the following quadratic equation: 5x^2 + 3x = 2x + 1 Solve this quadratic equation: 6a^2 + 13a + 6=0 Solve the quadratic equation: 3 x^2 + 10 x - 5 = 0. Solve the quadratic equation 7x^2 - 5 = 0. ...
Move all the expressions to the left side of the equation.( 3x^2+2x-4=0)Use the quadratic formula to find the solutions.( (-b± √(b^2-4(ac)))/(2a))Substitute the values ( a=3), ( b=2), and ( c=-4) into the quadratic formula and solve for ( x).( (-2± √(2^2...
例1: The scientist solved the mystery of the missing element.在这个例子中,“solve”与“mystery”进行了搭配使用,表示科学家解开了失踪元素的谜团。这种搭配在科学研究中非常常见,用于描述科学家通过实验和研究解决了某个科学难题。例2: The math teacher taught us how to solve the quadratic equation.在...
To solve a quadratic equation, we can use the ___ formula. A. linear B. quadratic C. cubic D. exponential 相关知识点: 试题来源: 解析 B。解二次方程可以用二次公式,quadratic 是二次的;linear 是线性的;cubic 是三次的;exponential 是指数的。反馈 收藏 ...
百度试题 结果1 题目Solve the equation by using the Quadratic Formula. 相关知识点: 试题来源: 解析 You getThe solution of the equation is such that. 反馈 收藏
Since a square root has two values, one positive and the other negative t2 + 6t + 1 = 0 has two solutions: t = -3 + √ 8 or t = -3 - √ 8 Solve Quadratic Equation using the Quadratic Formula 2.3 Solving t2+6t+1 = 0 by the Quadratic Formula . According to the Quadratic...
is not possible to find ,this equation has no solutions.These three examples illustrate that a quardretic equation can gave 2,1 or 0 solutions.The graphs below illustrate these graphically and show how the number of solutionsdepend on the sign of () which is part of the quardratic formula...
A. Solve each quadratic equation using the quadratic formula (14 points)1. x^2+6x+9=02. x^2+7x+10=03. x^2+4x-21=0 相关知识点: 试题来源: 解析 -3;-2;-5;-7;3 x^2+6x+9=0: 解:x=-3 x^2+7x+10=0: 解:x=-2, x=-5 x^2+4x-21=0: 解:x=-7, x=3...
Solve each equation using the quadratic formula. -4x^2+2x+3=0 相关知识点: 试题来源: 解析 x= (\ 1± √ (13))4 -4x^2+2x+3=0, so a=-4, b=2, c=3.x= (-(2)±√ (2^2-4(-4)(3)))(2(-4))= (-2± √ (52))(-8)= (\ 2± √ 4√ (13))8= (\ 2± 2√ (...